Continuation of Peritoneal Dialysis in Adult Kidney Transplant Recipients With Delayed Graft Function - Gardezi, Ali I. (Kidney Int Rep, 2021)
INTRODUCTION: Peritoneal dialysis (PD) has been used increasingly in past decade. Many of these patients undergo transplantation and may require dialysis for delayed graft function (DGF). The outcomes of DGF based on the post-transplantation dialysis modality are not well known. METHODS: We retrospectively reviewed all adult kidney transplant recipients (KTRs) from the University of Wisconsin School of Medicine and Public Health who developed DGF between November 2015 and April 2019. Patients were divided into those who received hemodialysis (HD) or PD during the DGF period. Immediate graft explant, DGF among living donor KTRs, or those requiring just a single dialysis treatment were excluded. RESULTS: Of 224 KTRs with DGF during the study period, 167 fulfilled our selection criteria. There were 16 patients in the PD and 151 in the HD group. Baseline characteristics were similar between the two groups, except diabetes was more prevalent in the HD group. Five of 16 PD patients had to be transitioned to HD. There was no difference in DGF duration, hospital length of stay, infectious or surgical complications, rejection at various time periods, graft function at last follow-up, or graft failure. In multivariate analysis, only rejection within the first year of transplantation (hazard ratio [HR]: 4.26; 95% confidence interval [CI]: 1.20–15.08; P = 0.02) and post-surgical complications (HR: 3.79; 95% CI: 1.03– 13.91; P = 0.04) were associated with death-censored graft failure (DCGF). The use of PD for treatment of DGF was not associated with DCGF. CONCLUSIONS: In carefully selected patients, PD can be continued safely for DGF without any effect on short-term or long-term transplant outcomes.